Does the Integration of Personalized Ultrasound Change Patient Management in Critical Care Medicine? Observational Trials. (18th December 2013) - Breitkreutz, Raoul; Campo delľ Orto, Marco; Hamm, Christian; Cuca, Colleen; Zechner, Peter M.; Stenger, Tanja; Walcher, Felix; Seeger, Florian H.
Abstract : Objective. To test the influence of personalized ultrasound (PersUS) on patient management in critical care. Design of the Study . Prospective, observational, and critical care setting. Four substudies compared PersUS and mobile ultrasound, work distribution, and diagnostic and procedural quality. Patients and Interventions . 640 patient ultrasound exams including 548 focused diagnostic exams and 92 interventional procedures. Main Outcome Measures . Number of studies, physician's judgement of feasibility, time of usage per patient, and referrals to echo lab. Results . Randomized availability of PersUS increased its application in ICU work shifts more than twofold from 33 to 68 exams mainly for detection and therapy of effusions. Diagnostic and procedural quality was rated as excellent/very good in PersUS-guided puncture in 95% of cases. Integrating PersUS within an initial physical examination of 48 randomized cases in an emergency department, PersUS extended the examination time by 100 seconds. Interestingly, PersUS integration into 53 randomized regular ward rounds of 1007 patients significantly reduced average contact time per patient by 103 seconds from 8.9 to 7.2 minutes. Moreover, it lowered the patient referral rate to an echo lab from 20% to 2% within the study population. Conclusions . We propose the development of novel ultrasound-based clinical pathways by integration of PersUS.